Cyclosporine and tacrolimus have inhibitory effects on toll‐like receptor signaling after liver transplantation. Issue 10 (24th September 2013) - Howell, Jessica; Sawhney, Rohit; Testro, Adam; Skinner, Narelle; Gow, Paul; Angus, Peter; Ratnam, Dilip; Visvanathan, Kumar
<x xml:space="preserve">Abstract</x> Toll‐like receptors (TLRs) play a key role in transplantation biology. The effect of immunosuppression on TLR function after liver transplantation is unknown. Peripheral blood mononuclear cells (PBMCs) from 113 post–liver transplant patients and 13 healthy controls were stimulated with TLR‐specific ligands [lipopolysaccharide (TLR4), pan‐3‐cys (P3C) (TLR2), Poly (I:C) (PIC) (TLR3), R848 (TLR7/8), and CpG (TLR9)] for 24 hours. PBMCs from 5 healthy controls were also cultured with therapeutic concentrations of cyclosporine A (CYA) and tacrolimus (TAC). Cytokine production was measured with enzyme‐linked immunosorbent assays and flow cytometry. PBMCs from patients on calcineurin inhibitors after liver transplantation produced less interleukin‐6 (IL‐6) and tumor necrosis factor α (TNFα) in response to TLR2 stimulation (IL‐6: P=0.02; TNFα: P=0.01), TLR4 stimulation (IL‐6: P=0.02; TNFα: P=0.01), and TLR7/8 stimulation (IL‐6: P=0.02; TNFα: P=0.02), compared with healthy controls. Both CD56bright and CD56dim natural killer (NK) cells from patients on calcineurin inhibitors also produced less interferon‐γ (IFNγ) with TLR7/8 stimulation compared with healthy controls (CD56bright: P=0.002; CD56dim: P=0.004). Similar findings were demonstrated in healthy PBMCs cultured with CYA (PBMCs: TLR2, IL‐6: P=0.005; TLR4, IL‐6: P=0.03, TNFα: P=0.03; TLR7/8, IL‐6: P=0.02, TNFα: P=0.01; CD56dim NK cells: TLR7/8, IFNγ: P=0.03). TAC impaired TLR4‐mediated IL‐6 and TNFα production by PBMCs (IL‐6; P = 0.02; TNFα P = 0.009). In conclusion, patients on calcineurin inhibitors had impaired inflammatory cytokine production in response to TLR2, TLR4, and TLR7/8 stimulation compared comparison with healthy controls. Importantly, TAC and CYA appear to have different effects on TLR signaling. Impaired TLR function has important repercussions for risk of infection, graft rejection, and disease recurrence after transplantation, and the different immunosuppressive profiles of CYA and TAC may guide the choice of therapy to improve disease outcomes. Liver Transpl 19:1099‐1107, 2013. © 2013 AASLD.